Effects of Continuing Education Incentives on Clinical Instructors. - Gildon, Bradford; Baldwin, Jonathan; Bagley, Jennifer E.; White, Robin; Mangrum, Marissa; Anderson, Stacy (Radiologic Technology)
Purpose To research whether the ability to earn continuing education (CE) credit for time spent teaching motivates radiologic science professionals to teach students in clinic and to assess whether sonographers, who earn CE credit for time teaching, have more positive attitudes toward teaching than those in modalities who do not earn CE credit for time spent teaching. Methods Researchers developed a 2-track digital survey and delivered it electronically and on paper to clinical instructors working at hospitals affiliated with Department of Medical Imaging and Radiation Sciences programs at the University of Oklahoma Health Sciences Center. Responses were collected for 2 weeks and then compared quantitatively using chi-square tests and logistic regression models. Qualitative results were examined for themes, and proportions among themes were reported. Results A total of 239 people responded, with 166 responses coming from individuals working in radiography, radiation therapy, nuclear medicine, and medical dosimetry, and 73 responses from sonography. Receiving CE credit did not result in a difference in teaching attitudes (χ² = 0.0004, DF = 1, P = .985). However, the non-CE credit--earning population showed a 12% increase in positive attitudes if allowed to earn CE credit in the future (95% CI; 0.08, 0.17). Discussion Student learning and performance in clinic directly are related to experiencing a positive learning environment. Factors other than CE credit appear to motivate instructors to teach students. Although the results of this study did not support the hypotheses, this study furthers the need to discuss whether offering CE credit for clinic instruction is something the profession should consider. Conclusion Clinical instructors who are willing to teach are the most desirable to students. Further evaluation of CE credit as an extrinsic motivating factor for clinical instructorship is important for providing the best positive learning environment for students.